Young people, agriculture, and employment in rural Africa - James Sumberg; Nana Akua Anyidoho; Michael Chasukwa; Blessings Chinsinga; Jennifer Leavy; Getnet Tadele; Stephen Whitfield; Joseph Yaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the current interest in addressing the problem of young people's unemployment in Africa through agriculture. Using notions of transitions and mobilities we set out a transformative work and opportunity space framework that privileges difference and diversity among work opportunities, rural areas and young people. We argue that policy and programmes that seek to engage young people with agriculture must be more realistic, rooted in more context-specific economic and social analysis, and appreciative of the variety of ways that rural men and women use agriculture to serve their needs and interests.
Keywords: J13; N57; O13; Q18; 330; young people; transformation; agriculture; entrepreneurialism